2002
DOI: 10.1089/105072502320908295
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a Mutation in the Thyroid Hormone Receptor β Gene Spontaneously Develop Thyroid Carcinoma: A Mouse Model of Thyroid Carcinogenesis

Abstract: The molecular genetic basis of thyroid carcinogenesis is not well understood. Most of the existing models of thyroid cancer only rarely show metastases, and this has limited progress in the understanding of the molecular events in thyroid cancer invasion and metastasis. We have recently generated a mutant mouse by introducing a dominant negative mutant thyroid hormone nuclear receptor gene, TRbetaPV, into the TRbeta gene locus. In this TRbetaPV mouse, the regulation of the thyroid-pituitary axis is disrupted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 20 publications
7
162
0
1
Order By: Relevance
“…Whereas the liganded TRb1 represses cyclin D1 expression, it has been reported that repression via the CRE is lost in the TRb1 mutant PV (Furumoto et al, 2005). The PV mutation was identified in a patient with thyroid hormone resistance syndrome and is tumorigenic in mice (Suzuki et al, 2002). It has been postulated that the lack of T3-dependent cyclin D1 repression by the PV mutant results in constitutive activation of cyclin D1 contributing to its tumorigenic effects (Furumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the liganded TRb1 represses cyclin D1 expression, it has been reported that repression via the CRE is lost in the TRb1 mutant PV (Furumoto et al, 2005). The PV mutation was identified in a patient with thyroid hormone resistance syndrome and is tumorigenic in mice (Suzuki et al, 2002). It has been postulated that the lack of T3-dependent cyclin D1 repression by the PV mutant results in constitutive activation of cyclin D1 contributing to its tumorigenic effects (Furumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, corepressor levels influence breast cancer progression (Peterson et al, 2007) and acquisition of tamoxifen resistance (Lavinsky et al, 1998), the aberrant recruitment of SMRT by the oncoprotein PML-RAR is a landmark in myeloid leukemias (Hong et al, 2001), down-regulation of SMRT can induce transformation of immortalized lymphoma cell lines (Song et al, 2005) and aberrant cytoplasmic distribution of NCoR and SMRT is a general trait of colorectal tumors (FernandezMajada et al, 2007). Moreover, in a recent study (Furuya et al, 2009), it has been shown that NCoR is a regulator of activation of PI3K signaling by the PV mutant TRb1 that causes development of metastastic thyroid carcinoma in mice (Suzuki et al, 2002), and that the corepressor could be considered as a novel tumor suppressor in this model of thyroid cancer.…”
Section: Antagonism Of Ras Responses By Trb1 S García-silva Et Almentioning
confidence: 99%
“…In a transgenic mouse model where a mutant thyroid hormone receptor ␤ gene (TR␤PV) was knocked-in, the activation of the PI3K/Akt pathway was determined following the interaction of TR␤PV with the p85␣ regulatory subunit of PI3K, and spontaneous development of FTCs was observed [81,82]. Several human tumor studies proposed that activation and nuclear localization of Akt1 is involved in the invasiveness and metastatic behavior of FTC triggered by the PI3K/Akt pathway [75].…”
Section: Targeting Pi3kmentioning
confidence: 99%
“…The availability of a mouse model of follicular thyroid carcinoma has provided an opportunity to dissect the molecular basis of this cancer (Suzuki et al, 2002;Ying et al, 2003a, b). This mutant mouse was created by a targeted mutation of thyroid hormone b receptor (TRbPV) via homologous recombination and the CreLoxP system (Kaneshige et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…PV has completely lost thyroid hormone (T3) binding and exhibits potent dominant-negative activity (Meier et al, 1992). Remarkably, as homozygous TRbPV mice (TRb PV/PV mice) age, they spontaneously develop follicular thyroid carcinoma through pathological progression resembling human thyroid cancer (Suzuki et al, 2002). One single patient homozygous for a mutant TRb has been reported and he died at a young age of unknown cause (Ono et al, 1991).…”
Section: Introductionmentioning
confidence: 99%